2021
DOI: 10.1016/j.trd.2021.102743
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance of shared micromobility and personal alternatives using integrated modal LCA

Abstract: The environmental performance of shared micromobility services compared to private alternatives has never been assessed using an integrated modal Life Cycle Assessment (LCA) relying on field data. Such an LCA is conducted on three shared micromobility services in Paris -bikes, second-generation e-scooters, and e-mopeds -and their private alternatives. Global warming potential, primary energy consumption, and the three endpoint damages are calculated. Sensitivity analyses on vehicle lifespan, shipping, servicin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 17 publications
0
62
0
Order By: Relevance
“…Perhaps the crucial concept of risk management in transport could aid in addressing the issue of life-cycle cost evaluations in the road planning and design process, which is particularly challenging owing to a lack of relevant data [61,62]. Moreover, life-cycle cost analysis, including pavement selection, could help to address the previously mentioned gap in the LCT approach to micromobility systems, which does not account for the impacts related to infrastructure and pavements [17,63]. The literature review even shows that, usually, investing more money "up front" reduces the global warming impact and life-cycle cost of pavements, in particular for bridges.…”
Section: Parallel Research Areas Of Micromobility Sustainability-soci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the crucial concept of risk management in transport could aid in addressing the issue of life-cycle cost evaluations in the road planning and design process, which is particularly challenging owing to a lack of relevant data [61,62]. Moreover, life-cycle cost analysis, including pavement selection, could help to address the previously mentioned gap in the LCT approach to micromobility systems, which does not account for the impacts related to infrastructure and pavements [17,63]. The literature review even shows that, usually, investing more money "up front" reduces the global warming impact and life-cycle cost of pavements, in particular for bridges.…”
Section: Parallel Research Areas Of Micromobility Sustainability-soci...mentioning
confidence: 99%
“…Moreover, the actual impacts on energy demand and GHG emissions over the entire life cycle are frequently insufficient for the first goal [16]. Life Cycle Assessment (LCA) studies on micromobility modes do not include the impacts related to pavements and infrastructure [17]. Furthermore, safety and health effects, including pedestrian and cyclist deaths or injuries, as well as equity, are regarded as critical issues in transport.…”
Section: Introductionmentioning
confidence: 99%
“…For bikes as vehicles on a standalone basis, studies on LCA found a carbon footprint of about 5 gCO2e/km [3,13], e.g., a 15 kg bike made mostly of steel at about 6 kgCO2e per kg and amortized over a life course of 20,000 km [75].…”
Section: Cyclingmentioning
confidence: 99%
“…The transport of people and goods is a prominent target since it mostly involves oil-fueled vehicles, especially cars and trucks [2]. The policies for transport decarbonization include not only the adoption of electric vehicles but also the sharing of cars under a variety of forms and modal shift from solo car usage to alternative modes [2]: the bus or the train to achieve scale economies in energy expenditure, or the "active" modes of walking and cycling which apparently involve no energy consumption -or little so in the case of e-bikes [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation